Acetylene Dicarboxylic Acid Diallyl Ester: A Versatile Monomer for Thiol-Ene Photocured Networks - ÇAKMAKÇI, EMRAH (WILEY-V C H VERLAG GMBH, 2021)
Thiol-ene photopolymerization (TEP) is a highly advantageous method for the curing of unsaturated monomers, and the design of novel monomers to be used in TEP is an active area of research. The feasibility and the versatility of novel acetylene dicarboxylic acid diallyl ester (ACDAE)-based monomers are synthesized and demonstrated. The electron deficient acetylenic core in ACDAE allows to apply three different click reactions, aza-Michael, thio-Michael, and metal-free azide-alkyne cycloaddition reactions, efficiently on it. Thus, three novel allylic monomers are synthesized and are used to prepare thiol-ene photopolymerized networks. All monomers are synthesized in good yields and structurally characterized by H-1 NMR and Fourier-transform infrared spectroscopy (FTIR) measurements. Thermal, thermomechanical, and mechanical properties, flame retardancy, transmittance, and the wettability of the networks are determined.
Keywords: acetylene dicarboxylic acid diallyl ester; aza-Michael; metal-free azide-alkyne cycloaddition reaction; thiol-ene photopolymerization; thio-Michael; CO-CURING AGENT; POLYMER NETWORKS; COVALENT IMMOBILIZATION; POLYTHIOETHER SYNTHESIS; HYBRID COATINGS; CLICK CHEMISTRY; EPOXY; FUNCTIONALIZATION; POLYESTER; THERMOSETS